2013
DOI: 10.1021/jm301564f
|View full text |Cite
|
Sign up to set email alerts
|

Strategies To Reduce hERG K+ Channel Blockade. Exploring Heteroaromaticity and Rigidity in Novel Pyridine Analogues of Dofetilide

Abstract: Drug-induced blockade of the human ether-a-go-go-related gene K(+) channel (hERG) represents one of the major antitarget concerns in pharmaceutical industry. SAR studies of this ion channel have shed light on the structural requirements for hERG interaction but most importantly may reveal drug design principles to reduce hERG affinity. In the present study, a novel library of neutral and positively charged heteroaromatic derivatives of the class III antiarrhythmic agent dofetilide was synthesized and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
2
40
1
1
Order By: Relevance
“…Therefore, it can be concluded that the binding site in the receptor imposes tight dimensional requirements for the size of the peptide linker and additional flexibility in the linker may lead to pronounce intra-cavitary blockade. Similar conclusions were reached in in-silico designs of minimally structured hERG1 blockers, as well as re-designed analogs of high-affinity blocker dofetilide [26], [27].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, it can be concluded that the binding site in the receptor imposes tight dimensional requirements for the size of the peptide linker and additional flexibility in the linker may lead to pronounce intra-cavitary blockade. Similar conclusions were reached in in-silico designs of minimally structured hERG1 blockers, as well as re-designed analogs of high-affinity blocker dofetilide [26], [27].…”
Section: Resultssupporting
confidence: 66%
“…Several recent studies emphasized importance of drug rigidity for efficient binding to channel with a reduced blockade [26], [27]. We investigated the effect of the peptide-like chain linker between benzene rings.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 19,20,24,25,[27][28][29][30][39][40][41][42][43][44][45][46] were newly synthesized in order to obtain compounds with various RT values besides a diverse range of K i and k on values. All other compounds were selected from our in-house library based on their distinct affinities and kinetic parameters, and synthesis of these compounds has been reported in our previously published studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The first series of compounds (S23a− e) were derived from commercially available 2,6-dibromopyridine and 1-alkynes with various lengths via a Sonogashira coupling reaction. 25 The final compounds (24, 25, and 27−29) were synthesized in relatively high yields by reduction of triple bonds to single bonds and methylation of neutral pyridines. 30 was obtained directly from S23e by methylation of the central nitrogen with a good yield of 94%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation